Hungarian Monitoring, 16 June 1989 . [Magyar rádiófigyelő], 1989. június 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Late night commentaries from Moscow, Prague, Warsaw and Tokyo on funeral ceremony Domestic Affairs: - Live broadcast from Heroes Square of funeral ceremony held for Imre Nagy and colleagues - International responses to day of mourning - Miklós Németh's statement to American TV ABC - Mother Theresa arrives in Budapest to open home of her missionary order to help the poor - Paris human rights conference: André Erdős rejects Romanian delegation's assertion that they called Romanian minorities policy "irreproachable" Economy: - Concept for developing tax system finalized in Finance Ministry Külpolitika: - Késő esti kommentárok a gyászszertartásról Moszkvából, Prágából, Varsóból, Tokióból Belpolitika: - Élő közvetítés Nagy Imre és sorstársainak Hősök terén megrendezett gyászszertartásáról - A gyásznap nemzetközi visszhangja - Németh Miklós nyilatkozata az ABC amerikai TV-társaságnak - Teréz Anya Budapestre érkezett, hogy misszionárius rendje házat nyisson a szegények szolgálatára - A párizsi emberjogi értekezleten Erdős André cáfolta a román delegátus állításait hazája kifogástalannak nevezett kisebbségi politikájáról Gazdaság: - A Pénzügyminisztériumban elkészült az adórendszer fejlesztésének koncepciója